Water, hydration, and health - Popkin, Barry M; D'Anci, Kristen E; Rosenberg, Irwin H (Nutrition reviews, 2010)
This review examines the current knowledge of water intake as it pertains to human health, including overall patterns of intake and some factors linked with intake, the complex mechanisms behind water homeostasis, and the effects of variation in water intake on health and energy intake, weight, and human performance and functioning. Water represents a critical nutrient, the absence of which will be lethal within days. Water's importance for the prevention of nutrition‐related noncommunicable diseases has received more attention recently because of the shift toward consumption of large proportions of fluids as caloric beverages. Despite this focus, there are major gaps in knowledge related to the measurement of total fluid intake and hydration status at the population level; there are also few longer‐term systematic interventions and no published randomized, controlled longer‐term trials. This review provides suggestions for ways to examine water requirements and encourages more dialogue on this important topic.